Neutrophil/lymphocyte ratio and other blood cell component counts are not associated with the development of postmolar gestational trophoblastic neoplasia. - Antonio Braga; Ana Clara Canelas; Berenice Torres; Izildinha Maesta; Luana Giongo Pedrotti; Marina Bessel; Ana Paula Vieira Dos Santos Esteves; Joffre Amim Junior; Jorge Rezende Filho; Kevin M Elias; Neil S Horowitz; Ross S Berkowitz (PLoS ONE, 2022)
Objective To relate preevacuation platelet count and leukogram findings, especially neutrophil/lymphocyte ratios (NLR) and platelet/lymphocyte ratios with the occurrence of gestational trophoblastic neoplasia (GTN) after complete hydatidiform mole (CHM) among Brazilian women. Methods Retrospective cohort study of patients with CHM followed at Rio de Janeiro Federal University, from January/2015-December/2020. Before molar evacuation, all patients underwent a medical evaluation, complete blood count and hCG measurement, in addition to other routine preoperative tests. The primary outcome was the occurrence of postmolar GTN. Results From 827 cases of CHM treated initially at the Reference Center, 696 (84.15%) had spontaneous remission and 131 (15.85%) developed postmolar GTN. Using optimal cut-offs from receiver operating characteristic curves and multivariable logistic regression adjusted for the possible confounding variables of age and preevacuation hCG level (already known to be associated with the development of GTN) we found that ≥2 medical complications at presentation (aOR: 1.96, CI 95%: 1.29-2.98, p<0.001) and preevacuation hCG ≥100,000 IU/L (aOR: 2.16, CI 95%: 1.32-3.52, p<0.001) were significantly associated with postmolar GTN after CHM. However, no blood count profile findings were able to predict progression from CHM to GTN. Conclusion Although blood count is a widely available test, being a low-cost test and mandatory before molar evacuation, and prognostic for outcome in other neoplasms, its findings were not able to predict the occurrence of GTN after CHM. In contrast, the occurrence of medical complications at presentation and higher preevacuation hCG levels were significantly associated with postmolar GTN and may be useful to guide individualized clinical decisions in post-molar follow-up and treatment of these patients.